Repair in Translation. Issue 1 (1st March 2020) - Grant, Jenna
Abstract: In this article, the author juxtaposes writing and conversation about care for, with, and in spite of technology in Cambodia. The scene is medical care, and the actors are radiologists, engineers, cadres, and X-ray machines. A radiologist is forced to repair an X-ray machine for doctors of the revolution; the pressure and constraints are almost unreal, yet his skill in repair affirms his humanity and the specialized knowledge and creativity required for problem solving. An engineer teaches repair as he fixes an old X-ray machine. He finds words and necessary tools are missing in Phnom Penh, a familiar story of lack, yet repair is material practice that enables improvisation in spite of linguistic and epistemic challenges. A radiologist, the same one from before, in the twilight of his life, questions the dominance of technologies within medical care and the deskilling of doctors. Juxtaposing these stories bolsters attention for the mundane and creative work of keeping things going in a "broken world, " in line with the ways that care and repair are mobilized in STS. It also shows how the radical potential of "broken world thinking" is circumscribed when a broken world is the one from which people are struggling to distance themselves. What we are left with are multiple, overlapping, fraught stories of modernity in which need, choice, and pleasure of repair all have a place.